MASSIVE OPEN ONLINE COURSE (MOOC) DALAM MENINGKATKAN KOMPETENSI LITERASI INFORMASI GURU PUSTAKAWAN SEKOLAH - Johan, Riche Cynthia (Universitas Pendidikan Indonesia, 2015)
Massive open online learning program course one form of technology-based learning is done online informationand to support the ownership of information literacy skills for library personnel. In the school library, information literacy is the ability to produce the form of practical problem solving to find information, use the information to share information with the information and communication technology. In particular, the problems that need to be analyzed in the context of information literacy learning for school library personnel are: Firstly, how to raise awareness for actively engaged, participatory and self have information literacy ?; Second, how understanding of library information literacy includes the identification of information needs, information retrieval, information use and sharing of information through a miniature of massive open onlinelearning course ?. In general, the methods used in this program is through the development of forms of learning and research on a limited scale. The next stage of knowledge transfer activities through a learning process, assignment and evaluation concludes openly and online.Keywords: Online Learning, Literacy, Personal Library.